2010
DOI: 10.1093/nar/gkq806
|View full text |Cite
|
Sign up to set email alerts
|

Alternative translation start sites are conserved in eukaryotic genomes

Abstract: Alternative start AUG codons within a single transcript can contribute to diversity of the proteome; however, their functional significance remains controversial. Here, we provide comparative genomics evidence that alternative start codons are under negative selection in vertebrates, insects and yeast. In genes where the annotated start codon (sAUG) resides within the suboptimal nucleotide context, the downstream in-frame AUG codons (dAUG) among the first ∼30 codon sites are significantly more conserved betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 40 publications
4
81
0
Order By: Relevance
“…In general, the phastCons score (between 0 and 1) gives a probability that each nucleotide belongs to a conserved element (see Material and Methods for detailed explanation). Overall, the human and mouse conservation plot indicated that the dTIS are highly conserved, with a mean conservation score of 0.97 (Ϯ 0.002, 95% confidence interval) and 0.97 (Ϯ 0.005) for respectively the Exon1 and ExonϾ1 groups compared with the dbTIS with a mean conservation score of 0.96 (Ϯ 0.01) and are thus indicative for the fact that the dTIS translation start sites are very well conserved within eukaryotic genomes in analogy to what was previously reported by Bazykin et al (87) using in silico predictive analyses and using in vivo GTI-seq experiments (33).…”
Section: Mapping Of the Translation Initiation Landscape In Human Andsupporting
confidence: 79%
“…In general, the phastCons score (between 0 and 1) gives a probability that each nucleotide belongs to a conserved element (see Material and Methods for detailed explanation). Overall, the human and mouse conservation plot indicated that the dTIS are highly conserved, with a mean conservation score of 0.97 (Ϯ 0.002, 95% confidence interval) and 0.97 (Ϯ 0.005) for respectively the Exon1 and ExonϾ1 groups compared with the dbTIS with a mean conservation score of 0.96 (Ϯ 0.01) and are thus indicative for the fact that the dTIS translation start sites are very well conserved within eukaryotic genomes in analogy to what was previously reported by Bazykin et al (87) using in silico predictive analyses and using in vivo GTI-seq experiments (33).…”
Section: Mapping Of the Translation Initiation Landscape In Human Andsupporting
confidence: 79%
“…Although we cannot formally exclude the possibility that this major KCP2 species results from the proteolytic processing of a longer form, our results indicate that the Met27 codon of human KCP2 mRNA is the principal site of translation initiation, and we conclude that this is most probably the case for the majority of vertebrates (supplementary material Fig. S2) (see also Bazykin and Kochetov, 2011;Kochetov, 2005).…”
Section: Expression Of Kcp2 By Leaky Ribosomal Scanningmentioning
confidence: 76%
“…One possibility is that the two forms are produced from one single transcript, with two alternative translation initiation sites, in a process termed leaky scanning. the use of alternative start codons to generate various protein variants is a conserved feature in eukaryotes [43]. examples for leaky scanning were reported for several proteins including human-insulin-degrading enzyme (IDe) [44] and human neuropeptide Y [45].…”
Section: Dpp9-l Is An Active Peptidasementioning
confidence: 99%